Th17 cells, γδ T cells and their interplay in EAE and multiple sclerosis. (February 2018) - McGinley, Aoife M.; Edwards, Sarah C.; Raverdeau, Mathilde; Mills, Kingston H.G.
Abstract: Experimental autoimmune encephalomyelitis (EAE) is an animal model of multiple sclerosis (MS) that shares many features with the human disease. This review will focus on the role of IL-17-secreting CD4 and γδ T cells in EAE and MS, the plasticity of Th17 cells in vivo and the application of these findings to the understating of the pathogenesis and the development of new treatments for MS. There is convincing evidence that IL-17-secreting CD4 T cells (Th17 cells) and IL-17-secreting γδ T cells play a critical pathogenic role in central nervous system (CNS) inflammation in EAE and MS. Indeed a significant number of the major discoveries on the pathogenic role of IL-17-secreting T cells in autoimmunity were made in the EAE model. These included the first demonstration that IL-23-activated IL-17-secreting T cells are the key T cells in driving autoimmune disease pathology. Although the early studies on IL-17 focused on Th17 cells, it was later demonstrated that γδ T cells were an important early source of IL-17 and IL-21 that helped amplify IL-17 production by Th17 cells in autoimmune diseases. Furthermore, it emerged that Th1 cells can also have encephalitogenic activity and that there was considerable plasticity in these T cell responses, with Th17 cells reverting to a Th1 phenotype in vivo . This questioned the pathogenic role of IL-17 and suggested that other cytokines, such as IFN-γ, GM-CSF and TNF, may be important. Nevertheless, biological drugs that target the IL-23-IL-17 pathway are highly effective in treating human psoriasis and are showing promise in the treatment of relapsing remitting MS and other T-cell mediated autoimmune diseases. Highlights: Th17 cells and IL-17-secreting γδ T cells are pathogenic in EAE and MS. IL-17-secreting γδ T cells kick start the inflammatory process in EAE. Pathogenic Th17 cells can revert to Th1-type cells in vivo in EAE. Drugs that target IL-23 and IL-17 pathways have potential for the treatment of MS.